مخاطر السيولة وأثرها على مردودية المصارف الإسلامية الكويتية: (دراسة قياسية بإستخدام بيانات السلاسل الزمنية المقطعية (2019- للفترة 2012 (Panel Data: Liquidity risks and its impact on the profitability of Kuwaiti Islamic banks: (econometrics study by using Panel Data Models during the period 2012-2019) - سايح حمزة; مناد بولنوار إلياس زكرياء (Journal of North African Economies, 2025)
This study aims to examine the effect of liquidity risk on the profitability of Kuwaiti Islamic banks during the period 2012-2019, using Panel data. The results resulted in a positive significant effect between the net liquidity gap and the profitability of Kuwaiti Islamic banks, and the presence of a negative significant effect between the rapid liquidity ratio and the profitability on these banks, in contrast, no effect was found between the bank’s ability to withstand liquidity shocks and the profitability of banks for the sample of the study.